P664 Bidirectional association between inflammatory bowel disease and psoriasis in a pediatric population: A nationwide insurance claim data analysis in South Korea. (21st January 2022) - Kim, D H; Cho, S I
Abstract: Background: Inflammatory bowel disease (IBD) and psoriasis are chronic inflammatory diseases and have been reported to have an association between them. However, most of the patients included in the previous reports were adults. As both diseases are related to each other, special consideration is required in managing each disease, as there is a high possibility of co-occurrence. In this regard, to figure out the association between the two diseases in childhood and adolescence is needed. Methods: A nationwide population-based retrospective cohort study was performed using the Korean National Health Insurance claims database. A birth cohort from January 2002 to December 2006. Claim data related to IBD and psoriasis was evaluated up to December 2019 and was analyzed to figure the association between the two diseases. Results: The datasets contained a total of 2, 347, 591 individuals. A total of 2, 444 IBD patients and 5, 165 psoriasis patients were identified. Thirteen patients had both IBD and psoriasis. Compared to the age and sex-matched control group, IBD patients showed a higher association of psoriasis (Odd ratios (ORs), 2.476; 95% confidence interval (CI), 1.240–4.945). In contrast, psoriasis patients did not show a statistically significant association compared to the control group (ORs, 1.857; 95% CI, 0.962–3.585). However, the proportion of patients with severe IBD was significantly higher (ORs, 6.000; 95% CI, 1.003–35.908). Conclusion: The association between IBD and psoriasis is observed in pediatric patients. Recognizing and early diagnosis of related diseases in children with IBD and psoriasis is necessary for better clinical outcomes